Characterization of 10-hydroxygeraniol dehydrogenase from catharanthus roseus reveals cascaded enzymatic activity in iridoid biosynthesis - Krithika, Ramakrishnan; Srivastava, Prabhakar Lal; Rani, Bajaj; Kolet, Swati P.; Chopade, Manojkumar; Soniya, Mantri; Thulasiram, Hirekodathakallu V. (Scientific Reports, 2015)
Catharanthus roseus [L.] is a major source of the monoterpene indole alkaloids (MIAs), which are of significant interest due to their therapeutic value. These molecules are formed through an intermediate, cis-trans-nepetalactol, a cyclized product of 10-oxogeranial. One of the key enzymes involved in the biosynthesis of MIAs is an NAD(P)(+) dependent oxidoreductase system, 10-hydroxygeraniol dehydrogenase (Cr10HGO), which catalyses the formation of 10-oxogeranial from 10-hydroxygeraniol via 10-oxogeraniol or 10-hydroxygeranial. This work describes the cloning and functional characterization of Cr10HGO from C. roseus and its role in the iridoid biosynthesis. Substrate specificity studies indicated that, Cr10HGO has good activity on substrates such as 10-hydroxygeraniol, 10-oxogeraniol or 10-hydroxygeranial over monohydroxy linear terpene derivatives. Further it was observed that incubation of 10-hydroxygeraniol with Cr10HGO and iridoid synthase (CrIDS) in the presence of NADP(+) yielded a major metabolite, which was characterized as (1R, 4aS, 7S, 7aR)-nepetalactol by comparing its retention time, mass fragmentation pattern, and co-injection studies with that of the synthesized compound. These results indicate that there is concerted activity of Cr10HGO with iridoid synthase in the formation of (1R, 4aS, 7S, 7aR)-nepetalactol, an important intermediate in iridoid biosynthesis.

Comprehensive metabolic and transcriptomic profiling of various tissues provide insights for saponin biosynthesis in the medicinally important Asparagus racemosus - Srivastava, Prabhakar Lal; Shukla, Anurag; Kalunke, Raviraj M. (Scientific Reports, 2018)
Asparagus racemosus (Shatavari), belongs to the family Asparagaceae and is known as a "curer of hundred diseases" since ancient time. This plant has been exploited as a food supplement to enhance immune system and regarded as a highly valued medicinal plant in Ayurvedic medicine system for the treatment of various ailments such as gastric ulcers, dyspepsia, cardiovascular diseases, neurodegenerative diseases, cancer, as a galactogogue and against several other diseases. In depth metabolic fingerprinting of various parts of the plant led to the identification of 13 monoterpenoids exclusively present in roots. LC-MS profiling led to the identification of a significant number of steroidal saponins (33). However, we have also identified 16 triterpene saponins for the first time in A. racemosus. In order to understand the molecular basis of biosynthesis of major components, transcriptome sequencing from three different tissues (root, leaf and fruit) was carried out. Functional annotation of A. racemosus transcriptome resulted in the identification of 153 transcripts involved in steroidal saponin biosynthesis, 45 transcripts in triterpene saponin biosynthesis, 44 transcripts in monoterpenoid biosynthesis and 79 transcripts in flavonoid biosynthesis. These findings will pave the way for better understanding of the molecular basis of steroidal saponin, triterpene saponin, monoterpenoids and flavonoid biosynthesis in A. racemosus.